2011
DOI: 10.1111/j.1939-1676.2011.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular and Saphenous Vein Thrombi Associated with Sepsis in a Quarter Horse Foal

Abstract: A 41-kg, 12-hour-old Quarter Horse filly presented to the Boren Veterinary Medical Teaching Hospital for a 12-hour history of weakness and recumbency. The mare had a history of premature lactation and presumptive placentitis, which was treated with trimethoprim-sulfamethoxazole by the referring veterinarian. The filly was born at 315 days gestation; parturition was unattended. The filly was found recumbent and unable to stand. Before referral, the attending veterinarian administered 1 L of colostrum via nasoga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Echocardiography could have been considered in this case for detection of systemic thrombus formation but is more indicated if there is a clinical suspicion of endocarditis (Banse et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Echocardiography could have been considered in this case for detection of systemic thrombus formation but is more indicated if there is a clinical suspicion of endocarditis (Banse et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Ultrasonographic monitoring of every catheter could be seen as excessive; however, application in high risk patients such as this foal could be appropriate, as early removal and application of therapy are the most important factors for successful treatment and outcome. Echocardiography could have been considered in this case for detection of systemic thrombus formation but is more indicated if there is a clinical suspicion of endocarditis (Banse et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Experimental bacteremia and endotoxemia induce intravascular fibrin deposition in kidneys, lungs, liver, and brain, manifesting clinically as disseminated intravascular coagulation (DIC), a syndrome frequently observed in septicemic and endotoxemic patients. 13 Consumptive coagulopathies have been observed in septicemic foals, [14][15][16][17] and in 1 study, evidence of DIC and microvascular thrombosis were identified in the tissues of 28/32 septic nonsurviving foals. 15 When compared with healthy foals, septic foals have lower aPC and ATIII activities and higher PAI-1, TNF-a, and interleukin-6 (IL-6) activities, suggesting that sepsis induces prothrombotic, antifibrinolytic shifts in hemostasis that may contribute to systemic hypercoagulation and DIC.…”
mentioning
confidence: 99%